Disrupting the memory of places induced by drugs of abuse weakens motivational withdrawal in a context-dependent manner - Taubenfeld, Stephen M. (National Academy of Sciences, 2010)
Addicts repeatedly relapse to drug seeking even after years of abstinence, and this behavior is frequently induced by the recall of memories of the rewarding effects of the drug. Established memories, including those induced by drugs of abuse, can become transiently fragile if reactivated, and during this labile phase, known as reconsolidation, can be persistently disrupted. Here we show that, in rats, a morphine-induced place preference (mCPP) memory is linked to context-dependent withdrawal as disrupting the reconsolidation of the memory leads to a significant reduction of withdrawal evoked in the same context. Moreover, the hippocampus plays a critical role in linking the place preference memory with the context-conditioned withdrawal, as disrupting hippocampal protein synthesis and cAMP-dependent-protein kinase A after the reactivation of mCPP significantly weakens the withdrawal. Hence, targeting memories induced by drugs may represent an important strategy for attenuating context-conditioned withdrawal and therefore subsequent relapse in opiate addicts.